SISTEM INFORMASI PURCHASE ORDER BERBASIS WEB DI PT HK-PATI - Elsamitia; Abu Bakar Sidik, Haris; Ponco Subagyo, Catur (POLITEKNIK PIKSI GANESHA, 2024)
PT HK-PATI Indonesia is a company that manufactures automotive components whose order process is via PO (Purchase Order) starting from the customer sending a purchase order form to the company via email, still doing it manually. The purpose of this research is to speed up the incoming order process by recommending a web-based application order application program so as to make employee performance fast and effective and the resulting information process is more accurate and timely than using incoming e-mail, reducing the efficiency of receiving orders. The initial stage of designing a development model uses the waterfall method and UML (Unified Modeling Language) as steps for designing a program. With this system, it is hoped that it will make it easier for companies to process data on purchase orders.